The end of cinema? A medium in crisis in the digital age - Gaudreault, André 1952-; Marion, Philippe (Columbia Univ. Press, 2015)
Introduction: The end of cinema? -- Cinema is not what it used to be -- Digitalizing cinema from top to bottom -- A brief phenomenology of 'digitalized' cinema -- From shooting to filming: the Aufhebung effect -- A medium is always born twice -- New variants of the moving image -- 'Animage' and the new visual culture -- Conclusion: A medium in crisis in the digital age
Keywords: Film; Gesellschaft; Philosophie; Motion pictures / Philosophy; Motion pictures / Technological innovations; Motion pictures / Social aspects; Digital media; Neue Medien; Zukunft